Microbial diversity in the floral nectar of seven Epipactis (Orchidaceae) species. Issue 4 (8th July 2013) - Jacquemyn, Hans; Lenaerts, Marijke; Tyteca, Daniel; Lievens, Bart
Abstract: Floral nectar of animal‐pollinated plants is commonly infested with microorganisms, yet little is known about the microorganisms inhabiting the floral nectar of orchids. In this study, we investigated microbial communities occurring in the floral nectar of seven Epipactis (Orchidaceae) species. Culturable bacteria and yeasts were isolated and identified by partially sequencing the small subunit (SSU) ribosomal RNA (rRNA) gene and the D1/D2 domains of the large subunit (LSU) rRNA gene, respectively. Using three different culture media, we found that bacteria were common inhabitants of the floral nectar of Epipactis . The most widely distributed bacterial operational taxonomic units (OTUs) in nectar of Epipactis were representatives of the family of Enterobacteriaceae, with an unspecified Enterobacteriaceae bacterium as the most common. In contrast to previous studies investigating microbial communities in floral nectar, very few yeast species (mainly of the genus Cryptococcus ) were observed, and most of them occurred in very low densities. Total OTU richness (i.e., the number of bacterial and yeast OTUs per orchid species) varied between 4 and 20. Cluster analysis revealed that microbial communities of allogamous species differed from those of autogamous and facultatively autogamous species. This study extends previous efforts to identify microbial communities in floral nectar and indicates that the floral nectar of the orchids investigated mainly contained bacterial communities with moderate phylogenetic diversity. Abstract : In this study, we describe the microbial communities in the floral nectar of seven Epipactis species. Despite previous claims that the floral nectar of orchids is characterized by the presence of several antimicrobial substances that possibly limit microbial growth, we found a wide variety of both bacterial and yeast species.